Vertical Slip Rates of Normal Faults Constrained by Both Fault Walls: A Case Study of the Hetao Fault System in Northern China - Xu, Dongsheng; He, Zhongtai; Ma, Baoqi; Long, Jianyu; Zhang, Hao; Liang, Kuan (Frontiers in Earth Science, 2022)
The slip rate is a fundamental kinematic parameter of active faults. Traditional methods using fault scarps or trenches may produce inaccurate estimates of a fault’s vertical slip rate. A normal fault’s vertical slip rate requires constraints from the hanging wall and footwall. Here, the vertical slip rate at each measuring point along the fault was calculated by the joint constraints of platforms in the footwall and boreholes in the hanging wall. Nine measuring points were selected along the Sertengshan piedmont fault. The vertical slip rates of this fault since 65 ka and 12 ka were 0.74-1.81 and 0.86-2.28 mm/a, respectively. Four measuring points were selected along the Wulashan piedmont fault. The vertical slip rates of this fault since 60 ka and 12 ka were 2.14-3.11 and 1.84-2.91 mm/a, respectively. Seven measuring points were selected along the Daqingshan piedmont fault; the vertical slip rates were 2.5-3.88 and 1.78-2.83 mm/a since 58 ka and 11 ka, respectively. Analysis of the slip rates, the elapsed time since the last palaeoearthquake and the mean recurrence interval of palaeoearthquakes on each fault segment on the northern margin of the Hetao Basin suggests that the Langshankou and Hongqicun segments of the Sertengshan piedmont fault are at higher risk of earthquakes than the other segments. Among the fault segments of the Wulashan piedmont fault, the Baotou segment is at the highest seismic risk. The seismic risk of the Tuyouxi segment of the Daqingshan piedmont fault should not be ignored, and the Tuzuoxi, Bikeqi and Hohhot segments have high seismic risk. Based on the findings and a dynamic model of the formation and evolution of the Ordos block, it is concluded that the depositional centre of the Hetao Basin has tended to migrate from west to east. The vertical force generated by deep material movement is the dominant factor leading to a greater vertical slip rate in the eastern portion of the northern margin of the Hetao Basin. The modern stress field in the Hetao Basin results in an increase in the vertical slip rate of faults from west to east along the northern margin of the basin.